9x-6=-12x

Simple and best practice solution for 9x-6=-12x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9x-6=-12x equation:


Simplifying
9x + -6 = -12x

Reorder the terms:
-6 + 9x = -12x

Solving
-6 + 9x = -12x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '12x' to each side of the equation.
-6 + 9x + 12x = -12x + 12x

Combine like terms: 9x + 12x = 21x
-6 + 21x = -12x + 12x

Combine like terms: -12x + 12x = 0
-6 + 21x = 0

Add '6' to each side of the equation.
-6 + 6 + 21x = 0 + 6

Combine like terms: -6 + 6 = 0
0 + 21x = 0 + 6
21x = 0 + 6

Combine like terms: 0 + 6 = 6
21x = 6

Divide each side by '21'.
x = 0.2857142857

Simplifying
x = 0.2857142857

See similar equations:

| 55.6-44.4= | | 14[3-(2-x)]+13x=3(9x+5)-1 | | 4x/38= | | 2f+3=11f-4 | | 3(x-9)=-12 | | 38=-43+x | | 44.4-38.2= | | -33=-3(2-2n)+3n | | 2a-(3)=9a-(10) | | 17x-8=4(4x+5)-12 | | 3m+2-4=10 | | 11(v+4)-2v=3(3v+4)-13 | | -0.9375+-9.375x+-3x^2+4.5625x^2=0 | | 2[5x-1]=3[x+11] | | -12=2(-3+x) | | x+x+(x+10)+(x+10)=272 | | -3(5d-6)=22 | | 4x(0.75x+1.25)= | | log(2x-1)+log(x+2)=1 | | 18-16=x/5 | | -24=-3(3+n) | | 9y-7=12y-13 | | 4x^2+(-0.75x+1.25)(-0.75x+1.25)+4xy-12x-6(-0.75x+1.25)+5=0 | | 7-8(1-3s)=21 | | 5x+(x+6)+5x+(x+6)=312 | | 7-8(1)3s=21 | | (5x-3)2=9 | | 2(x-1+x+x2+3)=7(2) | | x-(x+5)=15 | | x-1+x+x2+3=7 | | -33=3y-4y | | 5y-x=19 |

Equations solver categories